Quality of Briquettes Produced with Jatropha and Eucalyptus - Cynthia Patricia de Sousa Santos; Rosimeire Cavalcante dos Santos; Angélica de Cássia Oliveira Carneiro; Ana Flávia Neves Mendes Castro; Renato Vinícius Oliveira Castro; Sarah Esther de Lima Costa; Izabelle Rodrigues Ferreira Gomes; Krisnara Soares Mairinck (Floresta e Ambiente, 2020)
Abstract Our study aims to determine the energetic quality of residues from the manufacturing of jatropha and eucalyptus, as well as to evaluate the physical properties of the briquettes made with different proportions of these biomasses. The following proportions were used for this study: 100% eucalyptus; 75% eucalyptus; 50% jatropha and 50% eucalyptus; 75% jatropha; and 100% jatropha. The apparent density of the residues, the immediate chemical product, the highest calorific value (HCV), the apparent density, the energy density, the usable calorific value (UCV), the lowest calorific value (LCV), the breaking strength of the briquettes (FR) and the hydroscopic moisture balance (HMB) were verified. Although the energetic characteristics of the jatropha residues are not superior to those of eucalyptus, this biomass adds favorable mechanical characteristics to the briquettes comprised of greater proportions of jatropha to eucalyptus, guaranteeing the energetic properties of the briquette, as well as reducing the production cost.